MANAJEMEN KURIKULUM MELALUI GISIMAN: UPAYA STRATEGIS PENGUATAN PEMBELAJARAN NUMERASI DI SDN KABUPATEN PASURUAN - Ainul Yaqin; Ahmad Thohirin; Suyitno (STKIP Subang, 2026)
The low level of numeracy in public elementary schools in Pasuruan Regency, caused by rigid learning methods, necessitates adaptive curriculum management innovation. This study examines the implementation of GISIMAN (Giat Numerasi dengan Permainan) through a playful learning approach. Using a qualitative descriptive method based on best practices, the results indicate that the integration of interactive games effectively increases students' active engagement and eliminates psychological barriers toward mathematics. In addition to strengthening cognitive competence, GISIMAN simultaneously builds the Character Profile of Pancasila Students, particularly in the dimensions of mutual cooperation and critical thinking. The study concludes that GISIMAN is a strategic solution for transforming numeracy learning into a more enjoyable, meaningful, and contextual experience in elementary schools